PRONOMINA BAHASA KANUM SOTA - Sitti Mariati (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Kanum Sota Language is one of the regional languages contained in Papua Province with a small number of speakers. Kanum Sota language is spoken by the community of Kampung Sota, Merauke Regency, located in the border area of Indonesia with Papua New Guinea. This research is a field research. The data collection of this research using the method of conversation that is to do conversation with speakers as resource persons with the provocative technique as basic technique and face to face technique, and note technique as the next technique. This study was conducted to describe the pronouns of Kanum Sota language. Kanum Sota language recognizes three kinds of pronouns, namely (1) personal pronoun, (2) demonstrative pronoun, and (3) interrogative pronoun.